Development and validation of a tool to evaluate the quality of medical education websites in pathology - Raja H Alyusuf; Kameshwar Prasad; Ali M Abdel Satir; Ali A Abalkhail; Roopa K Arora (Elsevier, 2013)
Background: The exponential use of the internet as a learning resource coupled with varied quality of many websites, lead to a need to identify suitable websites for teaching purposes. Aim: The aim of this study is to develop and to validate a tool, which evaluates the quality of undergraduate medical educational websites; and apply it to the field of pathology. Methods: A tool was devised through several steps of item generation, reduction, weightage, pilot testing, post-pilot modification of the tool and validating the tool. Tool validation included measurement of inter-observer reliability; and generation of criterion related, construct related and content related validity. The validated tool was subsequently tested by applying it to a population of pathology websites. Results and Discussion: Reliability testing showed a high internal consistency reliability (Cronbach's alpha = 0.92), high inter-observer reliability (Pearson's correlation r = 0.88), intraclass correlation coefficient = 0.85 and κ =0.75. It showed high criterion related, construct related and content related validity. The tool showed moderately high concordance with the gold standard (κ =0.61); 92.2% sensitivity, 67.8% specificity, 75.6% positive predictive value and 88.9% negative predictive value. The validated tool was applied to 278 websites; 29.9% were rated as recommended, 41.0% as recommended with caution and 29.1% as not recommended. Conclusion: A systematic tool was devised to evaluate the quality of websites for medical educational purposes. The tool was shown to yield reliable and valid inferences through its application to pathology websites.